İngiltere’nin İstanbul Elçisi Thomas Roe’nun diplomatik yazışmaları (1621-1628) - Büyükaksoy, Ahmet (My University, 2012)
İngiltere’nin 1621-1628 yılları arasında Osmanlı Devleti nezdinde elçiliğini yapmış olan Thomas Roe’nun mektupları 1740 yılında Samuel Richardson tarafından derlenmiş ve The negotiations of Sir Thomas Roe in his embassy to the Ottoman Porte, from year 1621 to 1628 inclusive: containing a great variety of curious and important matters, relating not only to the affairs of Turkish Empire, but also to the those of the other states of Europe in that period; his correspondences with most illustious persons… and many useful and instructive particulars adlı eser oluşturulmuştur. Bu çalışma dönemin gerek Osmanlı gerek de Avrupa tarihi hakkında çok önemli bilgiler ihtiva etmektedir. Çalışmamızın konusu bu eserin

mektuplarının Türkçeye çevrilmesi ve değerlendirilmesidir. Baskıcının yaptığı derleme sırasında bazı mektuplardaki şifreler çözülmemiş, bu çalışmaya da yansımıştır. ABSTRACT The letters of Thomas Roe, who was the ambassador of England to the Ottoman Empire, was collected by Samuel Richardson in 1740 and thereby the work of The negotiations of Sir Thomas Roe in his embassy to the Ottoman Porte, from year 1621 to 1628 inclusive: containing a great variety of curious and important matters, relating not only to the affairs of Turkish Empire, but also to the those of the other sates of Europe in that period; his correspondences with most illustious persons… and many useful and instructive particulars was created. This work contains many imortant information for both Ottoman and the other European states. The subject of our work is the translation and examination of the letters that were written in English. During the collection made by the publisher some cyphers were not decyphered which reflected to our work.
Keywords: İstanbul (Türkiye)_Diplomatik Yazışma_İngiltere; Yeniçağ Tarihi